Obtenção e caracterização de revestimentos de fosfatos de cálcio sobre substrato de Ti pela técnica de eletrodisposíção - Santos, Pablo Eduardo Costa dos (2016)
This work proposed a system composed by calcium phosphate-pluronic coatings on titanium substrates using electrodeposition method. Calcium phosphates (CaP) are very attractive because they can be converted to the hydroxyapatite (HA) phase in biological fluid. The CaP are biocompatible and promote a better osseointegration due to their chemical similarity to the inorganic part of bone tissue. The biocompatible copolymer Pluronic F-127 (F-127) shows antiinflammatory action, possibility of morphological control during the synthesis of several materials, as well the capacity of avoid the bacterian biofilm formation. The electrodeposition process stands out from others due to obtaining uniform coatings on complex geometry parts, such as a Ti prosthesis or Ti-alloys, and presents low cost. The characterization of samples was performed by infrared spectroscopy with Fourier transformed (FTIR), X-ray diffraction (XRD) and scanning electron microscopy (SEM). Bands of phosphate groups onto Ti substrate were confirmed by FTIR analysis. XRD analysis showed that the coatings presented different crystalline phases, depending on the conditions employed that were: Octacalcium phosphate (OCP) - Ca8(HPO4)2(PO4)4.5H2O; dicalcium phosphate dihydrate (DCPD) - CaHPO4.2H2O and anhydrous dicalcium phosphate (DCPA), CaHPO4, all of them precursors of HA. The morphology of coating surfaces, observed by SEM, of samples without F-127 (control) was plates and plates with radial growth, distinct from the morphology of the samples containing F-127, which were cobblestone, thick needles parallel to the substrate or fibrillary with dimensions of 24-57 µm in length. Gravimetric analysis after sample calcination revealed that the coatings present around 7.7 wt% F-127; while microbiological tests with S. aureus showed that the samples obtained by adding F-127 reduces bacterial adhesion. These systems have great potential to be used in increasing biocompatibility, osseointegration and minimize infections related to prosthesis.